An Expert Consensus Statement on the Management of Large Chondral and Osteochondral Defects in the Patellofemoral Joint. Issue 3 (26th March 2020) - Chahla, Jorge; Hinckel, Betina B.; Yanke, Adam B.; Farr, Jack; Bugbee, William D.; Carey, James L.; Cole, Brian J.; Crawford, Dennis C.; Fleischli, James E.; Getgood, Alan; Gomoll, Andreas H.; et al.
Background: Cartilage lesions of the patellofemoral joint constitute a frequent abnormality. Patellofemoral conditions are challenging to treat because of complex biomechanics and morphology. Purpose: To develop a consensus statement on the functional anatomy, indications, donor graft considerations, surgical treatment, and rehabilitation for the management of large chondral and osteochondral defects in the patellofemoral joint using a modified Delphi technique. Study Design: Consensus statement. Methods: A working group of 4 persons generated a list of statements related to the functional anatomy, indications, donor graft considerations, surgical treatment, and rehabilitation for the management of large chondral and osteochondral defects in the patellofemoral joint to form the basis of an initial survey for rating by a group of experts. The Metrics of Osteochondral Allografts (MOCA) expert group (composed of 28 high-volume cartilage experts) was surveyed on 3 occasions to establish a consensus on the statements. In addition to assessing agreement for each included statement, experts were invited to propose additional statements for inclusion or to suggest modifications of existing statements with each round. Predefined criteria were used to refine statement lists after each survey round. Statements reaching a consensus in round 3 were included within the final consensus document. Results: A total of 28 experts (100% response rate) completed 3 rounds of surveys. After 3 rounds, 36 statements achieved a consensus, with over 75% agreement and less than 20% disagreement. A consensus was reached in 100.00% of the statements relating to functional anatomy of the patellofemoral joint, 88.24% relating to surgical indications, 100.00% relating to surgical technical aspects, and 100.00% relating to rehabilitation, with an overall consensus of 95.5%. Conclusion: This study established a strong expert consensus document relating to the functional anatomy, surgical indications, donor graft considerations for osteochondral allografts, surgical technical aspects, and rehabilitation concepts for the management of large chondral and osteochondral defects in the patellofemoral joint. Further research is required to clinically validate the established consensus statements and better understand the precise indications for surgery as well as which techniques and graft processing/preparation methods should be used based on patient- and lesion-specific factors.